Wnt7a Promotes the Occurrence and Development of Colorectal Adenocarcinoma - Li, Congcong; Dou, Xiaowei; Sun, Jiahuan; Xie, Min; Li, Hongli; Cui, Peilin (Frontiers in Oncology, 2021)
Objective: The expression of Wnt7a in colorectal cancer tissues and cell lines was analyzed, and the effect of Wnt7a on the proliferation of colorectal cancer cells was studied, so as to confirm the relationship between Wnt7a and the occurrence and development of colorectal cancer.Methods:1.Immunohistochemical method was used to compare the expression of Wnt7a in different tissues and its relationship with the clinicopathology of colorectal adenocarcinoma.2.The expression levels of Wnt7a in colorectal cancer cell lines HT-29 and HCT 116 were detected by qRT-PCR.3.The down-regulated Wnt7A expression vector was constructed, and the down-regulated Wnt7A expression cell line was established. The regeneration ability of cancer cells was detected by stem cell ball formation assay, and the influence of plate cloning assay on the proliferation ability of colorectal cancer cells was detected..Results:1. The positive rates of Wnt7a in normal colorectal mucosa, colorectal adenoma and colorectal adenocarcinoma tissues gradually increased,Wnt7a are closely related to the degree of colorectal adenocarcinoma differentiation, lymph node metastasis and Duke stage.2.The expression level of Wnt7a in colorectal cancer cells was higher than that in normal colorectal epithelial cells.3The down-regulation of Wnt7A reduced the proliferation ability of colorectal cancer cells.Conclusions:Wnt7a promotes the occurrence and development of colorectal adenocarcinoma. Key words: Colorectal cancer,Wnt7a,occurrence,development